2020
DOI: 10.1186/s13256-020-02544-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary colon adenocarcinoma with choriocarcinoma differentiation: a case report and review of the literature

Abstract: Background Choriocarcinoma is an aggressive malignancy of trophoblastic tissue, typically of gestational etiology. Sporadic, nongestational cases are rarely found outside of the gonads. There are only 31 cases of primary choriocarcinoma of the colon reported in the literature. As a consequence of their rarity and aggressive nature, timely diagnosis and effective treatment have proved challenging, and prognosis is very poor. For that reason, we present a rare case with prolonged survival in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 33 publications
(20 reference statements)
0
24
0
Order By: Relevance
“…Bina et al found that patients with intestinal metastases from gestational choriocarcinoma inevitably have a combination of pulmonary and hepatic metastases [ 17 ]. However, a review of 31 reported cases of primary intestinal choriocarcinoma revealed that 14 cases had pulmonary metastases, and 23 cases had liver metastases, of which 8 cases had liver metastases only [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bina et al found that patients with intestinal metastases from gestational choriocarcinoma inevitably have a combination of pulmonary and hepatic metastases [ 17 ]. However, a review of 31 reported cases of primary intestinal choriocarcinoma revealed that 14 cases had pulmonary metastases, and 23 cases had liver metastases, of which 8 cases had liver metastases only [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is usually a transition zone between the two tissue types, in which the adenocarcinoma component is composed of tall columnar cells. As the tumor spreads and metastases, the adenocarcinoma features gradually decrease, and the choriocarcinoma features gradually increase [ 1 , 35 , 39 ]. As such, liver metastasis from primary intestinal choriocarcinoma often only have choriocarcinoma components under a microscope.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of cases of carcinoma with a germ cell tumor component, such as choriocarcinoma and YST, have been reported in various organs, including, but not limited to, the stomach 6 , gallbladder 7 , ovary and endometrium 810 , and urinary bladder. 11 In the colon, although both are rare, choriocarcinoma 1 is more frequently reported than YST. 25 Seemingly more common is colorectal adenocarcinoma with enteroblastic differentiation, 12,13 recently reported in case series.…”
Section: Discussionmentioning
confidence: 99%
“…Serum markers such as alpha-fetoprotein (AFP) and human chorionic gonadotropin (hCG) may be elevated in these cases. In the large intestine, a small number of adenocarcinoma cases with choriocarcinoma component have been reported, 1 but cases with yolk sac tumor component are exceedingly rare. [2][3][4][5] Herein, we report a case of recurrent colon cancer with a yolk sac tumor component and evidence of shared TP53 and APC mutations in the primary and recurrent lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Colon adenocarcinoma (COAD) is a malignant tumor that occurs in the colon or rectum (1,2), and ranks third in morbidity and second in mortality among all cancers worldwide. In Europe, approximately 250,000 new patients are diagnosed with COAD each year, accounting for about 9% of all malignancies (3,4).…”
Section: Introductionmentioning
confidence: 99%